Moderating Effect of Technostress Inhibitors on the Relationship between Technostress Creators and Organisational Commitment (Jurnal Teknologi (Sciences & Engineering), 2014)
This study aims to examine the moderating effect of technostress inhibitors on the relationship between technostress creators and organisational commitment among academic librarians in the Malaysian public universities. It considers how literacy facilitation, technical support, and involvement facilitation influence the strength of the relationship between technostress creators and organisational commitment. Multiple regression analysis and hierarchical multiple regression analysis were utilised to test the relationship and the moderating effect among the variables. The findings revealed that collectively, technostress creators significantly explained 13.1 percent of the variance in organisational commitment.Â  Techno-overload and techno-uncertainty were found to have significant positive relationship with organisational commitment. As for the moderating effect, both literacy facilitation and involvement facilitation did not act as moderator in the relationship between technostress creators and organisational commitment. Nevertheless, technical support was found to moderate the relationship between techno-overload and organisational commitment. All the technostress inhibitors were, however, found to be significant predictors for organisational commitment. This study demonstrates that a certain amount of stress is essential in enhancing employeeâ€™s commitment towards organisation. Moreover, it reveals that the existence of literacy facilitation, technical support, and involvement facilitation is crucial in boosting organisational commitment of academic librarians in the Malaysian public universities.